Teachers’ attitudes towards applying the projects method in the first cycle schools A field study in the first cycle schools in Lattakia - أبوسيف وفاء; منال سلطان (Latakia University Journal - Arts and Humanities Sciences Series, 2023)
The aim of the research is to identify the female teachers’ attitudes towards applying the projects method in the first cycle schools as it is one of the most important methods and strategies of active learning And to identify its advantages and the obstacles that limit the application of this method in the schools of the first cycle from the point of view of the teachers of the first cycle, and to address the research problem, the researcher used a questionnaire that contained (37) paragraphs distributed on three dimensions: (knowledge of the foundations of the projects method - the advantages of using the method Projects in the school - negatives and obstacles to using the method of projects in the school). For it, and its stability was confirmed by applying it to an exploratory sample that included (40) male and female teachers. The research ended with the following results: - Lack of knowledge of the female teachers of the basics of the projects method, and their poor awareness of its positives and advantages, and they find it difficult to use it, and their attitudes are negative towards it. - The more courses the teacher follows, the more she knows the foundations of the projects method, the less feeling of its negatives, and the better her attitudes towards its application. In the light of the results, recommendations were reached, the most important of which are: Increasing interest in training female teachers during service to use active learning methods and strategies in general and the projects method in particular, encouraging female teachers to use the projects method because of its great role in acquiring knowledge among learners.